Lean computing for the cloud - Bauer, Eric ([Princeton, NJ] : IEEE Press/Wiley, 2016)
Applies lean manufacturing principles across the cloud service delivery chain to enable application and infrastructure service providers to sustainably achieve the shortest lead time, best quality, and value This book focuses on lean in the context of cloud computing capacity management of applications and the physical and virtual cloud resources that support them. Lean Computing for the Cloud considers business, architectural and operational aspects of efficiently delivering valuable services to end users via cloud-based applications hosted on shared cloud infrastructure. The work also focuses on overall optimization of the service delivery chain to enable both application service and infrastructure service providers to adopt leaner, demand driven operations to serve end users more efficiently. The book's early chapters analyze how capacity management morphs with cloud computing into interlocked physical infrastructure capacity management, virtual resource capacity management, and application capacity management problems. The middle chapters frame cloud capacity management as a lean thinking problem, lay out strategies for applying lean thinking best practices across the cloud service delivery chain, and apply key lean insights from other industries. Later chapters discuss lean reserve capacity, lean demand management, optimal power management, and quantitative performance metrics of lean capacity management, which can be used to methodically drive continuous improvement of lean cloud computing deployments. The final chapter summarizes the book's insights on lean strategies to minimize waste across the cloud computing service delivery chain. . Applies lean thinking across the cloud service delivery chain to recognize and minimize waste. Leverages lessons learned from electric power industry operations to operations of cloud infrastructure. Applies insights from just-in-time inventory management to operation of cloud based applications. Explains how traditional, Information Technology Infrastructure Library (ITIL) and Enhanced Telecom Operation Map (eTOM) capacity management evolves to lean computing for the cloud This book is geared toward professionals with business, operational, architectural, development, and quality backgrounds in the information and communication technology industry. Eric Bauer is Reliability Engineering Manager in the IP Platforms Group of Alcatel-Lucent. Before focusing on reliability engineering, Mr. Bauer spent two decades designing and developing embedded firmware, networked operating systems, internet platforms, and optical transmission systems. He has been awarded more than a dozen US patents, and has authored several books such as Service Quality of Cloud-Based Applications, Reliability and Availability of Cloud Computing, and Design for Reliability: Information and Computer-Based Systems, all of which were published by Wiley-IEEE Press. Mr. Bauer earned his BS in Electrical Engineering from Cornell University and MS in Electrical Engineering from Purdue University.
10. Lean Cloud Capacity Management Performance Indicators 167 -- 10.1 Perfect Capacity Metrics 168 -- 10.2 Capacity Management Metrics 172 -- 10.3 Infrastructure Commitment Metrics 173 -- 10.4 Waste Metrics 174 -- 10.4.1 Reserve Capacity Waste Metrics 174 -- 10.4.2 Excess Application Capacity Metrics 175 -- 10.4.3 Excess Online Infrastructure Capacity Metrics 175 -- 10.4.4 Excess Physical Infrastructure Capacity Metrics 175 -- 10.4.5 Inadequate Capacity Metrics 175 -- 10.4.6 Infrastructure Overhead Waste Metrics 176 -- 10.4.7 Capacity Management Overhead Waste Metrics 176 -- 10.4.8 Resource Overhead Waste Metrics 176 -- 10.4.9 Power Management Overhead Waste Metrics 177 -- 10.4.10 Workload Migration Metrics 177 -- 10.4.11 Complexity Overhead Metrics 178 -- 10.4.12 Resource Allocation Failure Metrics 178 -- 10.4.13 Leaking and Lost Resources 179 -- 10.4.14 Waste Heat Metrics 179 -- 10.4.15 Carbon Footprint Metrics 180 -- 10.5 Key Principle Indicators 180 -- 10.6 Cost of Poor Quality 181 -- 10.7 Metrics and Service Boundaries 182 -- 10.8 Measurements and Maturity 183 -- 10.9 Chapter Review 185 -- 11. Summary 187 -- 11.1 Cloud Computing as a Service Delivery Chain 187 -- 11.2 Lean Cloud Computing 190 -- 11.3 Reimagining Cloud Capacity 192 -- 11.4 Lean Demand Management 195 -- 11.5 Lean Reserves 197 -- 11.6 Lean Infrastructure Service Provider Considerations 198 -- 11.7 Lean Application Service Provider Considerations 198 -- 11.8 Lean Infrastructure Commitment 199 -- 11.9 Visualizing Perfect Capacity 201 -- 11.10 Lean Cloud Computing Metrics 203 -- 11.11 Concluding Remarks 204 -- References 207 -- About the Author 211 -- Index 213.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed March 21, 2016).
John Wiley and Sons
Keywords: Cloud computing; Infonuagique; COMPUTERS -- Computer Literacy; COMPUTERS -- Computer Science; COMPUTERS -- Data Processing; COMPUTERS -- Hardware -- General; COMPUTERS -- Information Technology; COMPUTERS -- Machine Theory; COMPUTERS -- Reference; Cloud computing